2004
DOI: 10.1099/vir.0.79781-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent isolates of parapoxvirus of Finnish reindeer (Rangifer tarandus tarandus) are closely related to bovine pseudocowpox virus

Abstract: Short CommunicationRecent isolates of parapoxvirus of Finnish reindeer (Rangifer tarandus tarandus) are closely related to bovine pseudocowpox virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 21 publications
(14 reference statements)
4
50
0
Order By: Relevance
“…3 (data not shown). This confirms the proposition from previous studies of partial gene sequences that PCPV and ORFV are genetically more closely related to each other than either of them is to BPSV (Inoshima et al, 2001;Thomas et al, 2003;Tikkanen et al, 2004;Hosamani et al, 2006). This is despite BPSV and PCPV sharing the same bovine host, whereas the natural hosts of ORFV are sheep and goats.…”
Section: Comparison Of Predicted Ppv Protein Sequencessupporting
confidence: 80%
See 2 more Smart Citations
“…3 (data not shown). This confirms the proposition from previous studies of partial gene sequences that PCPV and ORFV are genetically more closely related to each other than either of them is to BPSV (Inoshima et al, 2001;Thomas et al, 2003;Tikkanen et al, 2004;Hosamani et al, 2006). This is despite BPSV and PCPV sharing the same bovine host, whereas the natural hosts of ORFV are sheep and goats.…”
Section: Comparison Of Predicted Ppv Protein Sequencessupporting
confidence: 80%
“…The aetiological agent has been identified as a parapoxvirus (PPV). It was demonstrated that two outbreaks of disease, one in 1992-1993 and one in 1999-2000, were apparently caused by different species of PPV (Tikkanen et al, 2004). The former, more severe outbreak with approximately 400 dead and about 2800 affected reindeer, was caused by a virus closely related to orf virus (ORFV), whereas the latter outbreak was caused by a virus showing notable partial sequence similarity to pseudocowpoxvirus (PCPV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ORFVs were isolated from cases of bovine papular stomatitis in cattle and some BPSVs were isolated from sheep 15 . Moreover, both ORFV and BPSV cause pustular dermatitis in Japanese serows (Capricornis crispus) 6,7 and both ORFV and PCPV also cause papular stomatitis in Finnish reindeer (Rangifer tarandus tarandus) 19 . In addition, experimental transmission of parapoxvirus from the Japanese serow to sheep, goats and cattle has succeeded 11,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemics have occurred in these areas since December 1984, and 155 of 402 serows (39.6%) captured from December 1984 to March 1985 were clinically affected [40]. Tikkanen et al reported that a recent outbreak of PPV infection in Finnish reindeer (Rangifer tarandus tarandus; 1999 to 2000) was caused by pseudocowpox virus, a species of the genus Parapoxvirus, whereas an earlier outbreak (1992 to 1994) was caused by orf virus (ORFV), a prototype species of PPV [42]. Sequence analyses of the viral envelope gene indicate that contagious pustular dermatitis in Japanese serows is mainly caused by ORFV [18,19].…”
mentioning
confidence: 99%